Microbial stowaways: Waterbirds as dispersal vectors of aquatic pro‐ and microeukaryotic communities. (12th May 2022) - Szabó, Beáta; Szabó, Attila; Vad, Csaba F.; Boros, Emil; Lukić, Dunja; Ptacnik, Robert; Márton, Zsuzsanna; Horváth, Zsófia
Abstract: Aim: Waterbirds are important dispersal vectors of multicellular organisms; however, no study to date has focused on their potential role in dispersing aquatic microbial communities. We explicitly studied endozoochory of prokaryotes and unicellular microeukaryotes by waterbirds using DNA metabarcoding. By directly comparing the dispersed set of organisms to the source pool of a natural metacommunity, we aimed at a realistic estimate of the importance of waterbird zoochory for natural microbial communities. Location: Temporary saline soda pans in Austria and Hungary. Taxon: Prokaryotes and unicellular microeukaryotes. Methods: In 2017 and 2018, water samples were collected from a network of 25 temporary ponds along with fresh droppings of five waterbird species including the dominant greylag goose ( Anser anser ). Prokaryotic and microeukaryotic communities were identified via 16S and 18S rRNA gene amplicon sequencing. After quality filtering of sequence reads, pro‐ and microeukaryotic amplicon sequence variant (ASV) compositions were compared between the aquatic and dropping samples, across years and waterbird species. Results: 28% of the dominant aquatic prokaryotic and 19% of the microeukaryotic ASVs were transported by A. anser . ASV richness was lower, but compositional variation was higher in A. anser droppings than in aquatic communities, probably resulting from stochastic pick‐up from multiple aquatic habitats. The composition of prokaryotic ASVs in bird droppings differed among the 2 years and reflected the actual aquatic communities. The dispersed set of microbes were largely similar among the waterbird species except for the planktivore filter‐feeder northern shoveler ( Spatula clypeata ), which dispersed more microeukaryotes than the other waterbirds. Main conclusions: Using an amplicon sequencing approach to characterize aquatic microorganisms in waterbird droppings and in the associated environment, our study provides strong evidence for endozoochory of natural communities. These results imply that waterbirds may be crucial in maintaining ecological connectivity between aquatic habitats at the level of microbial communities.